Nasal Carriage and Antibiotic Resistance Patterns of Staphylococcus aureus: A Case Study on the Nursing Students of Islamic Azad University of Eghlid Branch - Arezoo Tavakoli (Iranian Journal of Medical Microbiology, 2017)
Background and Aim: Staphylococcus aureus is an important cause of nosocomial infections. Many people are carriers for S. aureus in some parts of their body such as nose. In general, the population of carriers is higher among hospital staffs such as nurses who harbour antibiotic resistant staphylococcus strains which can be transmitted to patients. The aim of this study was to identify and evaluate the nasal carriage of S. aureus and determination of their antibiotic resistance patterns in a statistical population of nursing students in the Islamic Azad University of Eghlid Branch during 2014-2016. Materials and Methods: The relevant data were obtained using a questionnaire and the samples were then taken by rotating a moist cotton swab inside both nasal cavities of the nursing students. S. aureus strains were isolated and confirmed using conventional tests such as gram staining, catalase, coagulase and culture on DNase and Manitol salt agar. Antimicrobial susceptibility patterns against different antibiotics such as ampicillin, erythromycin, tetracycline, and chloramphenicol were carried out using Kirby-Bauer disk diffusion. Results and Conclusions: Out of the 216 students, 68 (%31.4) were nasal carriers of S. aureus. The results revealed that the highest and lowest antibiotic resistances rates were found against penicillin (%94.1) and ciprofloxacin (%3), respectively. A large number of students are nasal carriers of S. aureus which can increase the incidence of nosocomial infections. Therefore, it is recommended that screening and treatment for S. aureus be done for all the students and staff which are in direct contact with patients in hospitals.